Phyto-fabrication of silver nanoparticles and their catalytic dye degradation and antifungal efficacy - Githala, Chanda Kumari; Raj, Shani; Dhaka, Anita; Mali, Suresh Chand; Trivedi, Rohini (Frontiers in Chemistry, 2022)
The biogenic synthesis of silver nanoparticles (AgNPs) and their potent application against dye degradation and phytopathogens are attracting many scientists to nanotechnology. An attempt was made to synthesize silver nanoparticles using Plantago ovata leaf extract and test their effectiveness in removing organic dyes and antifungal activity. In the present study, stable AgNPs were synthesized from 0.1 mM AgNO3 and authenticated by observing the color change from yellow to red-brown, which was confirmed with wavelength UV-Vis spectrophotometer detection. The crystalline nature of the particles was characterized by x-ray diffraction (XRD) patterns. Furthermore, the AgNPs were characterized by high-resolution transmission electron microscope (TEM) and scanning electron microscope (SEM) investigations. Atomic force microscopy (AFM) and Raman spectra were also used to confirm the size and structure of the synthesized AgNPs. The elemental analysis and functional groups responsible for the reduction of AgNPs were analyzed by electron dispersive spectroscopy (EDS) and fourier transform infra-red spectroscopy (FTIR), respectively. A new biological approach was taken by breaking down organic dyes such as methylene blue and congo red. The AgNPs effectively inhibit the fungal growth of Alternaria alternata. This could be a significant achievement in the fight against many dynamic pathogens and reduce dye contamination from waste water.